Evaluasi Rekrutmen Pengawas Tempat Pemungutan Suara (PTPS) dalam Pemilu Serentak 2019 - Faisal Andri Mahrawa; Irfan Prayogi (Jurnal Adhyasta Pemilu, 2019)
This paper is intended to examine the recruitment pattern carried out by Bawaslu to bring PTPS to the 2019 Simultaneous Elections. The research location was conducted in two regions namely Sunggal District and Percut Sei Tauan District, Deliserdang Regency. By understanding various aspects ranging from the regulatory side to the technical implementation of recruitment, found various obstacles that resulted in the quality of PTPS, ranging from age limits, educational boundaries, community enthusiasm to regional factors that cause PTPS presented less professional. Using the descriptive- analysis method, data sources were collected through interviews and literature studies related to the PTPS recruitment process. As an evaluation and recommendation, this paper reviews several aspects, namely regulation, promotion and outreach, provision of intensive supervision functions, and transparency of recruitment to be considered in welcoming the next election.